(untitled) (Fiep Bulletin - online, 2014)
The present work is characterized as a theoretical inquiry and a descriptive analysis on games in the education for way the thought of different theoreticians, Huizinga, Kishimoto, Friedmann among others that they approach this content under different approaches, between which: social, antropologycal, pedagogical and psychological the approach. The games are objects of studies in different worried areas of knowing in investigating, analyzing, or either, to reflect on its varied conceptions and aspects. Of this form, one meets, easily, research and writings related the games from philosophical, antropologycal, psychological, psicanalitycal, biological, educational analyses, among others. For this reason, innumerable concepts of games exist depending on ` lens ’ and the objectives of that they define it. For in such a way, we will describe some statements on games established us in that more they are come close to our thought on what it is such activity. We remember that definitions and concepts definitive and are not limited therefore, depend on the context where if it carries through the reading of the reality to be analyzed. The games are objects of studies in different worried areas of knowing in investigating, analyzing, or either, to reflect on its varied conceptions and aspects. Of this form, research and writings meet, easily, related the games from philosophical, antropologycal, psychological, psicanalytical, biological, educational analyses, among others. For this reason, innumerable concepts of games exist depending on ` lens ’ and the objectives of that they define it.